Mistakes in external medical document handling - Drobnik, Jarosław; Susło, Robert; Trnka, Jakub; Muszyńska, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2008)
There is a significant increase in the role of cooperation between medical professionals of various specialties from various medical institutions in the process of treating every single patient, as well as in the use of medical data by various non-medical institutions. This in turn increases the importance of medical external documents in information exchange and the consequences of emerging mistakes. Aiming at improvement of information exchange effectiveness, several medical document standards have been defined by legal rules. It should be kept in mind that all doctors both fill in medical documents and receive documents filled in by others, and therefore they are susceptible to make many possible mistakes involving medical documents.